Effects of Nursing Position on Transformational Leadership Practices. (February 2015) - Herman, Susan; Gish, Mary; Rosenblum, Ruth
Abstract : OBJECTIVE: This study sought to identify significant differences in nursing leadership strengths by position title. BACKGROUND: Recent reports show aspects of transformational leadership (TL) related to position, age, and educational level. This study focuses on differentiating the strength of leadership practices across the range of nursing management positions. METHODS: The Leadership Practices Inventory—Self-assessment survey, and a variety of demographic questions, were used to anonymously poll voluntary members of the Association of California Nurse Leaders. RESULTS: Nursing positions of director level and above were strongest in leadership practices. Those at manager and below were identified as needing additional leadership development. LPI-S subscales Enable Others to Act and Model the Way were strongest. CONCLUSION: Those at the manager level and below will benefit most from additional education and training. Even upper levels of management would gain from enhancing the LPI practices of Challenge the Process and Inspire a Shared Vision. Abstract : Supplemental Digital Content is available in the text.